1971
DOI: 10.1111/j.1748-1716.1971.tb05105.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Inhibition of the Mechanical Response of the Isolated Rat and Guinea‐Pig Vas Deferens to Pre‐ and Postganglionic Nerve Stimulation

Abstract: Repeated periods with prolonged nerve stimulation (30 s) of the isolated vas deferens tended to depress especially the initial, rapid phase of subsequent contractions. The following findings led to the conclusion that the inhibition was induced by prostaglandin (PG)‐like material, released from the organ on nerve stimulation: 1. The inhibition was immediately abolished on washing of the organ. 2. It appeared faster in an organ bath of small volume than in one of a greater. 3. It was possible to transfer the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1973
1973
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…ETYA has been shown to simultaneously decrease the efflux of prostaglandins and increase the outflow of noradrenaline in response to sympathetic nerve stimulation in the rabbit heart (Samuelsson & Wennmalm, 1971) and cat spleen . Similar results were obtained in the guinea-pig vas deferens where ETYA inhibited prostaglandin efflux and increased the response to (Swedin, 1971;Hedqvist & von Euler, 1972b (Chanh et al, 1972) and guinea-pig vas deferens (Fredholm & Hedqvist, 1973).…”
Section: Discussionsupporting
confidence: 73%
“…ETYA has been shown to simultaneously decrease the efflux of prostaglandins and increase the outflow of noradrenaline in response to sympathetic nerve stimulation in the rabbit heart (Samuelsson & Wennmalm, 1971) and cat spleen . Similar results were obtained in the guinea-pig vas deferens where ETYA inhibited prostaglandin efflux and increased the response to (Swedin, 1971;Hedqvist & von Euler, 1972b (Chanh et al, 1972) and guinea-pig vas deferens (Fredholm & Hedqvist, 1973).…”
Section: Discussionsupporting
confidence: 73%
“…It has been reported that repeated periods of prolonged electrical field stimulation of the guinea-pig vas deferens result in the release of PGE2-like material which is able to inhibit both phases of contraction, with the second phase being inhibited to a lesser extent (Swedin, 1971a;Hedqvist & von Euler, 1972). Inhibitors of prostaglandin synthesis, such as eicosatetraynoic acid (ETYA) and indomethacin, sometimes produce slight increases in the contractions of the guinea-pig vas deferens produced by electrical field stimulation following the acute addition of the inhibitor to the organ bath (Swedin, 1971a;Hedqvist & von Euler, 1972;Fujita et al, 1992;Christian & Poyser, 1994). These findings indicate that the quantities of PGE2 released from the guineapig vas deferens during a short period of electrical field stimulation are too small to have any appreciable inhibitory effect on the contractions produced.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, endogenous PGE produced by field stimulation of the guinea-pig vas deferens (Swedin, 1971a;Hedqvist & von Euler, 1972) had a greater inhibitory effect on the first phase than on the second phase of contraction (Swedin, 1971a). More recent studies have shown that PGE2 selectively inhibits the fast phase of contraction of the rat and guinea-pig vas deferens (Bedwani & Blanning, 1983;Venkova & Radomov, 1988;Hata et al, 1991).…”
Section: Introductionmentioning
confidence: 92%
“…This conclusion is reinforced by the results of Holmes, Horton & Main (1963) and Weiner & Kaley (1969) who showed in various preparations that prostaglandin injections or topical application diminished the effects of nerve stimulation, noradrenaline or angiotensin. Since prostaglandin release may also have a regulatory function on the sympathetic innervation of the heart Hedqvist, Stjarne & Wennmalm, 1970;Wennmalm & Stjarne, 1971) and the vas deferens (Swedin, 1971;Hedqvist & von Euler, 1972), Hedqvist's hypothesis may have a much wider application than to the sympathetic innervation of the spleen.…”
Section: Discussionmentioning
confidence: 99%